Boosting Catalysis of Pd Nanoparticles in MOFs by Pore Wall Engineering: The Roles of Electron Transfer and Adsorption Energy. Issue 30 (11th June 2020) - Chen, Dongxiao; Yang, Weijie; Jiao, Long; Li, Luyan; Yu, Shu‐Hong; Jiang, Hai‐Long
Abstract: The chemical environment of metal nanoparticles (NPs) possesses significant influence on their catalytic performance yet is far from being well understood. Herein, tiny Pd NPs are encapsulated into the pore space of metal–organic frameworks (MOFs), UiO‐66‐X (X = H, OMe, NH2, 2OH, 2OH(Hf)), affording Pd@UiO‐66‐X composites. The surface microenvironment of the Pd NPs is readily modulated by pore wall engineering, via the functional group and metal substitution in the MOFs. Consequently, the catalytic activity of Pd@UiO‐66‐X follows the order of Pd@UiO‐66‐OH > Pd@UiO‐66‐2OH(Hf) > Pd@UiO‐66‐NH2 > Pd@UiO‐66‐OMe > Pd@UiO‐66‐H toward the hydrogenation of benzoic acid. It is found that the activity difference is not only ascribed to the distinct charge transfer between Pd and the MOF, but is also explained by the discriminated substrate adsorption energy of Pd@UiO‐66‐X (–OH < –2OH(Hf) < –NH2 < –OMe < –H), based on CO‐diffuse reflectance infrared Fourier transform spectra and density‐functional theory (DFT) calculations. The Pd@UiO‐66‐OH, featuring a high Pd electronic state and moderate adsorption energy, displays the highest activity. This work highlights the influence of the surface microenvironment of guest metal NPs, the catalytic activity of which is dominated by electron transfer and the adsorption energy, via the systematic substitution of metal and functional groups in host MOFs. Abstract : Pd nanoparticles (NPs) encapsulated into UiO‐66‐X (X = H, OMe, NH2, 2OH, 2OH(Hf)) show drastically different activities toward the hydrogenation of benzoic acid. This work highlights the influence of the surface microenvironment of guest metal NPs, the catalytic activity of which is dominated by electron transfer and the adsorption energy, via the systematic modification of host metal–organic frameworks (MOFs).